[tex]a)\\\\podstawa\ graniastoslupa\ to\ trojkat\ prostokatny : \\przyprostokatna:\ a=4\\przyprostokatna:\ b=5\\wysokosc\ graniastoslupa:\ \ H=5 \\\\ objetosc\ graniastoslupa:\\\\V=P_{p}*H\\\\pole\ podstawy:\\\\P_{p}=\frac{1}{2}ab=\frac{1}{\not{2}^1}*\not{4}^2*5=10\ [j^2] \\\\V=10*5=50\ [j^2][/tex]
[tex]b)\\\\podstawa\ graniastoslupa\ to\ trojkat\ rownoramienny : \\podstawa:\ a=8\\ ramie\ :\ b=5\\wysokosc\ grabiastoslupa:\ \ H=4\\\\obliczamy\ wysokosc\ podstawy:\\\\h^2+(\frac{a}{2})^2=b^2\\\\h^2=b^2-(\frac{a}{2})^2\\\\h^2=5^2-4^2\\\\h^2=25-16\\\\h^2=9\\\\h=\sqrt{9}=3[/tex]
[tex]objetosc\ graniastoslupa:\\\\V=P_{p}*H\\\\pole\ podstawy:\\\\P_{p}=\frac{1}{2}ah=\frac{1}{\not{2}^1}*\not{8}^4* 3=12\ [j^2] \\\\V=12*4=48\ [j^2][/tex]